2022
DOI: 10.7759/cureus.27406
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Quality of YouTube Videos on Adhesive Capsulitis

Abstract: IntroductionYouTube is the most popular video-based source of information on the Internet. It is accessed by over 1 billion users, which approximates to almost one-third of all Internet users. Orthopaedic video content published on YouTube is not screened and does not go through an editorial process, and most videos do not have information about authorship or appropriate references. Users who do not have the knowledge to assess the accuracy and reliability of the source may be misinformed about their medical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 10 publications
5
19
0
5
Order By: Relevance
“…In general, YouTube videos proved to be a poor online source for information regarding RSA, as shown by the poor quality scores attained. This falls in line with other YouTube-based studies in the literature that reported a low quality of information for orthopedic-related pathologies and procedures [ 7 , 16 , 20 , 21 , 24 ]. The unrestricted ability to upload videos and the lack of editorial evaluation on accuracy and comprehensiveness of content are potential contributors to the low scores exhibited in our study [ 8 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In general, YouTube videos proved to be a poor online source for information regarding RSA, as shown by the poor quality scores attained. This falls in line with other YouTube-based studies in the literature that reported a low quality of information for orthopedic-related pathologies and procedures [ 7 , 16 , 20 , 21 , 24 ]. The unrestricted ability to upload videos and the lack of editorial evaluation on accuracy and comprehensiveness of content are potential contributors to the low scores exhibited in our study [ 8 ].…”
Section: Discussionsupporting
confidence: 90%
“…A maximum score of five indicates excellent quality and flow. Although the GQS assessment is unvalidated, this tool has been used in numerous YouTube-based studies in the orthopedic literature [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, this method has been used before. 10,12 At the same time, although we evaluated the adhesive capsulitis videos by expanding the search terms in this study, we assume that we obtained similar data to the findings of Tang et al 9 The internet has made it easier than ever to access information on any topic imaginable. However, this also means a lot of misinformation and disinformation is available online.…”
Section: Discussionsupporting
confidence: 69%
“…19,34 However, the present study reflects the findings of other studies evaluating YouTube as a source of information pertaining to ACL, meniscus, kyphosis, and adhesive capsulitis. 5,9,21,35 While the content uploaders should assume responsibility for the quality of their videos, the poor quality of medically related TikTok videos could stem from other factors. TikTok relies on short video playtime and engagement times that may not allow for appropriate citation of sources or thorough discussion of rationale, risks, benefits, and safety precautions.…”
Section: Discussionmentioning
confidence: 99%